Batrachideinae (Orthoptera: Caelifera: Tetrigidae): an overview of the most diverse tetrigids of the Neotropical region - Silva, Daniela Santos Martins; Cadena-Castañeda, Oscar J.; Pereira, Marcelo Ribeiro (Zootaxa, 2021)
The Batrachideinae subfamily is a well-defined and taxonomically stable taxon, with a pantropical distribution and an important representation in the Neotropical region. In this study, the characters and distributions of the genera and species are discussed based on a morphological analysis and a key to genera of the American Batrachideinae is also provided. New synonymies are established: Tettigidea Scudder, 1862 = Eotetrix Gorochov, 2012 syn. nov.; Batrachidea mucronata (Saint-Fargeau & Serville, 1825) = Tettigidea granulosa Bruner, 1913 syn. nov.; Batrachidea planus (Hancock, 1907) = Batrachidea brevis (Hancock, 1909) syn. nov.; Tettigidea lateralis (Say, 1824) = Tettigidea nicaraguae Bruner, 1895 syn. nov.; Tettigidea lateralis (Say, 1824) = Tettigidea annulipes Bruner, 1910 syn. nov.; Tettigidea cuspidata Scudder, 1875 = Tettigidea corrugata Bruner, 1910 syn. nov.; Tettigidea cuspidata Scudder, 1875 = Tettigidea multicostata Bolívar, 1887 syn. nov.; Tettigidea chapadensis Bruner, 1910 = Tettigidea costalis Bruner, 1910 syn. nov.; Tettigidea chapadensis Bruner, 1910 = Tettigidea hancocki Bruner, 1910 syn. nov.; Tettigidea intermedia Bruner, 1910 = Tettigidea subatera Bruner, 1910 syn. nov.; Tettigidea scudderi Bolívar, 1887 = Tettigidea steinbachi Bruner, 1920 syn. nov. Three species are transferred from the genus Tettigidea to the genus Paxilla Bolívar, 1887: Paxilla mexicana (Hancock, 1915) comb. nov., Paxilla tecta (Morse, 1900) comb. nov., Paxilla nigra (Morse, 1900) comb. nov.; Tettigidea unicornis (Gorochov, 2012) comb. nov. is transferred from the genus Eotetrix Gorochov, 2012 to Tettigidea, and Batrachidea planus (Hancock, 1907) comb. nov. from Tettigidea to Batrachidea Serville, 1838. Five new species groups (lateralis, armata, cuspidata, paratecta and scudderi) are recognized in the genus Tettigidea. Neotype of Tettigidea lateralis lateralis is designated. Keys to the Batrachideinae genera and species of the most diverse American genera (Tettigidea and Paxilla) are also provided.